2001
DOI: 10.1161/hs0901.095602
|View full text |Cite
|
Sign up to set email alerts
|

Parenchymal Hyperdensity on Computed Tomography After Intra-Arterial Reperfusion Therapy for Acute Middle Cerebral Artery Occlusion

Abstract: Background and Purpose-The purpose of the present study was to assess the incidence and clinical significance of the intraparenchymal hyperdense areas on the posttherapeutic CT scan just after intra-arterial reperfusion therapy. Methods-Seventy-seven patients with acute middle cerebral artery occlusion were studied prospectively with posttherapeutic CT. Hyperdense areas were classified into three groups: those in the lentiform nucleus, insular cortex and cerebral cortex. We investigated the incidence of hyperd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

20
103
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(126 citation statements)
references
References 27 publications
20
103
2
Order By: Relevance
“…In contrast, all 7 patients with contrast extravasation, a hyperdense lesion with maximum HU Ͼ90 that persisted on follow-up CT scan, developed parenchymal hematoma with clinical deterioration. Nakano et al 7 reported that the rapid disappearance of hyperdense areas, which is analogous to contrast enhancement in this study, on early posttherapeutic CT scans was never associated with symptomatic hemorrhage.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…In contrast, all 7 patients with contrast extravasation, a hyperdense lesion with maximum HU Ͼ90 that persisted on follow-up CT scan, developed parenchymal hematoma with clinical deterioration. Nakano et al 7 reported that the rapid disappearance of hyperdense areas, which is analogous to contrast enhancement in this study, on early posttherapeutic CT scans was never associated with symptomatic hemorrhage.…”
Section: Discussionsupporting
confidence: 74%
“…6 Hemorrhagic transformation with deterioration of neurological symptoms is the major complication of intra-arterial thrombolytic therapy; a frequency between 10% and 15.4% has been observed. 2,4,5,7 After completion of angiography and thrombolytic therapy, a nonenhanced CT scan is usually performed to investigate the possibility of hemorrhagic lesion. In the literature, a hyperdense lesion seen on posttherapeutic, nonenhanced CT scans after intra-arterial thrombolysis has been described as either hemorrhage or extravasation of contrast medium given during angiographic procedures performed during thrombolysis.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Mericle et al (15) have suggested that extravasation of contrast medium could be defined as a hyperdense area with a maximal HU measurement over 90 and/or disappearance of the hyperdensity on a repeated CT obtained within 24 hours. Nakano et al (16) have described the rapidly clearing hyperdense areas as evidence of ex- travasation of the contrast medium. In the present study, contrast extravasation was measured between 90 and 100 HU in comparison with the surrounding blood clot where contrast extravasation measured 60 to 70 HU.…”
Section: Discussionmentioning
confidence: 99%
“…19 Patients receiving intraarterial reperfusion therapy for stroke can also show transient hyperattenuation of the lentiform and insular cortex secondary to interstitial contrast extravasation. 27 Finally, because the hyperdensities in diabetic patients with HC-HB may resolve slowly or persist for years, 28 these may reflect previous hyperglycemia-induced injury. MR imaging may also reveal abnormal putaminal signal with or without involvement of the caudate and globus pallidus.…”
Section: Hemichorea-hemiballismus In Non-ketotic Hyperglycemiamentioning
confidence: 99%